Front End da inovação de processo: proposta de um modelo para uma empresa do ramo de mineração - Junior Freire Coelho (2018)
The Front End of Innovation is the initial subprocess of the innovation process. In the context of process innovations, can be defined as the activities conducted before the concept of a new process to be implemented in the production process. Since the Front End of innovation is the foundation of successful innovation and organizations increase their chances of developing innovations by improving this subprocess, and the lack of studies related to the Front End of process innovation, which is the main type of innovation in process industries, such as mining industry. Added to the fact that the literature presents generic models, in which it is difficult for organizations to apply these studies to their innovation processes. The importance of studies that seek to propose applicable Front End models of process innovation is justifiable. In this context, this paper proposes a Front End model of process innovation, specific to an iron ore mining company in Brazil. For that, a preliminary model was proposed based on the analysis of the Front End models of innovation identified in the literature, and the experience of the author of the mining industry. Subsequently, this model was subjected it to a set of validation by a group of professionals who work directly with the development of innovations in the production process of an iron ore mining company, which resulted in the proposal of an adapted model. The proposed model includes five elements, the opportunity, the idea, the concept, the drivers of innovation, and the agents of influence. The interaction of these elements occurs through the four subphases of the model. The process starts with an idea and / or opportunity and results in a concept of a process innovation.